1994
DOI: 10.1113/jphysiol.1994.sp020389
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of respiratory and cardiovascular changes induced by systemic hypoxia in the rat: the roles of adenosine.

Abstract: 1. In ten spontaneously breathing, Saffan-anaesthetized rats (group I), respiratory and cardiovascular responses evoked by 10 min periods of hypoxia (arterial partial pressure of 02, Pa,02, 33 mmHg) were recorded before and after the administration of the adenosine receptor antagonist 8-phenyltheophylline (8-PT, 10 mg kg-' i.v.). Similar experiments were performed on nine constantly ventilated rats (group II; Pa02, 29 mmHg) with arterial partial pressure of CO2 (Pa,co2) held constant.2. In group I, hypoxia ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 22 publications
(50 reference statements)
11
63
1
Order By: Relevance
“…On the other hand, the lung stretch receptors with vagal afferents do contribute to the tachycardia, but not to the peripheral vasodilatation (62). Indeed, when ventilation was kept constant by artificial ventilation, then hypoxia induced bradycardia, but with substantial vasodilatation in skeletal muscle (60). By considering these results together with the effects of various antagonists of the sympathetic nervous system, we have concluded that the primary bradycardia of hypoxic stimulation of carotid chemoreceptors is opposed both by the secondary effects of hyperventilation on lung stretch receptors and by the ability of central nervous hypoxia to increase cardiac sympathetic activity (56,60,62).…”
Section: The Gradual Effects Of Hypoxiamentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the lung stretch receptors with vagal afferents do contribute to the tachycardia, but not to the peripheral vasodilatation (62). Indeed, when ventilation was kept constant by artificial ventilation, then hypoxia induced bradycardia, but with substantial vasodilatation in skeletal muscle (60). By considering these results together with the effects of various antagonists of the sympathetic nervous system, we have concluded that the primary bradycardia of hypoxic stimulation of carotid chemoreceptors is opposed both by the secondary effects of hyperventilation on lung stretch receptors and by the ability of central nervous hypoxia to increase cardiac sympathetic activity (56,60,62).…”
Section: The Gradual Effects Of Hypoxiamentioning
confidence: 99%
“…Thus, when ventilation begins to fall, this exacerbates the fall in PaO 2 and the peripheral vasodilatation and bradycardia that are caused by the local effects of hypoxia, so potentiating the fall in arterial pressure. Once the arterial pressure is below the autoregulatory range, then cerebral blood flow falls, the O 2 supply to the brain is further reduced and the central neural hypoxia is exacerbated so that the central respiratory neurones are further depressed (60).…”
Section: A Positive Feedback Loop?mentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine has been implicated as a potential mediator (Runold et al, 1989;Thomas and Marshall, 1994;Schmidt et al, 1995;Chau and Koos, 1999;Johansson et al, 2001). However, we recently demonstrated that adenosine release in the medullary regions involved in respiratory control, nucleus tractus solitarii and rostral ventrolateral medulla (VLM), occurs too late to be responsible for the initiation of hypoxia-induced depression of the respiratory activity .…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence implicate adenosine as a mediator for hypoxia-induced depression of respiration. Hypoxic respiratory depression is reduced by the administration of adenosine receptor antagonists (Runold et al, 1989;Thomas and Marshall, 1994;Schmidt et al, 1995;Chau and Koos, 1999) or in mice lacking adenosine A 1 receptor (Johansson et al, 2001). During hypoxia, adenosine levels rise in the VLM in the cat (Richter et al, 1999).…”
Section: Release Of Atp In the Ventral Medulla During Hypoxia In Ratsmentioning
confidence: 99%